Kesalahan Calon Guru Matematika dalam Menggunakan Ukuran Pemusatan: Pengabaian Variansi - Tamba, Kimura Patar; Siahaan, Meiva Marthaulina Lestari; Appulembang, Oce Datu (Jurnal Elemen, 2021)
The measure of the center is an essential topic in statistics. Pre-service mathematics teachers must have the ability to select and use measures of center. The inability to use and select appropriate center measures indicates a low understanding of center measures. Meanwhile, research on the ability to use and select the center's appropriate measures is very limited. This study explores the sources of error for pre-service mathematics teachers in using and selecting the appropriate measures of center. This study involved 177 pre-service mathematics teachers. This research is a qualitative study using the interpretive paradigm. Data were collected using a test containing two problems and clinical interviews. Data were analyzed qualitatively using grouping participant responses based on ways of thinking and ways of understanding to use and select center measures. The results showed that pre-service mathematics teachers could not select an appropriate measure of centers because they were too focused on measures of centers while ignoring the variance. In order to be able to select an appropriate measure of centers because variance must be considered simultaneously. The implication of this study results is the need for a learning approach that introduces concurrent measures of centers with data variance.